ANALISIS PENERAPAN GEMA HAJI PRA BELAJAR DALAM DIMENSI PROFIL PELAJAR PANCASILA ABAD 21 SDN 1 KEMBANG SARI - Ahmad Fauzan; Donna Boedi Maritasari; Laili Nurhayati Puadi; Putri Novianti; Azan Nuraini; Nurulya Hanifah; Kusmawaty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Islamic education is education that aims to form the complete Muslim person, develop all human potential both physically and spiritually, foster a harmonious relationship between every human being with Allah, humans and the universe. Educators can only guide the growth or survival of the religious powers that exist in children, so that they can improve their life behavior and develop children's religious character. Gema Hajj is a series of religious activities carried out by all students and teachers of SDN 1 Kembang Sari, East Lombok, NTB. Hajj echoes are carried out every day in each class before learning takes place. Hajj echoes are usually preceded by duha prayers, followed by dhikr and prayer, after that followed by memorizing a short letter. In this article, the literature observation method is used. This research will focus on the application of pre-learning Gema Haji analysis in the profile dimensions of 21st century Pancasila students at SDN 1 Kembang Sari, East Lombok, NTB. . Religious activities are conscious and planned efforts to prepare students to know, understand, believe, be devout, have noble morals, through guidance, teaching, training and the use of experience. Through Gema Hajj activities, it is a series of religious activities to teach or train students to gain knowledge and believe, appreciate and practice the teachings of the Islamic religion.